Analysis of the Contribution of Motor Vehicle Tax Revenue (Pkb) Through the Mobile Samsat Program to Tax Revenue at the Regional Revenue Management Regional Technical Implementation Unit (Uptd Ppd) in Minahasa - Karwur, Natanael; Sondakh, Jullie; Pangerapan, Sonny (East Asian Journal of Multidisciplinary Research, 2024)
Motor Vehicle Tax is the largest source of revenue for Local Original Revenue.As people's need for motorized vehicles increases, so does the people's purchasing power for motorized vehicles. Not only people in urban areas, but people who live in rural areas need motorized vehicles. The purpose of this study is to ascertain if the motor vehicle tax revenue has increased in tandem with the rise in the purchasing power of the public as a result of the samsat program. The descriptive method was the analytical approach employed in this investigation. The study's findings demonstrate how inadequate the Samsat Program is. People who reside distant from the headquarters can still be reached by the Samsat program, nevertheless.